THE USE OF INTERROGATIVE SENTENCES AND ANSWERS TO THEM IN EDUCATIONAL SITUATIONS AT RUSSIAN LANGUAGE LESSONS IN AN UZBEK SCHOOL - Khudayberdiyeva Muazzam Zaynobidinovna (American Journals Publishing, 2023)
The article deals with the question of the use of interrogative sentences and answers to them in educational situations. For the effective use of question-answer structures in the lessons of the Russian language and literature, it is necessary to consider educational situations from the point of view of the use of interrogative sentences for organizing a lesson.
Keywords: types of sentences, dialogue, monologue, motivation, cognitive activity, content components.